2012
DOI: 10.1371/journal.pone.0038250
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Soybean Flowering Genes

Abstract: Flowering is an important agronomic trait that determines crop yield. Soybean is a major oilseed legume crop used for human and animal feed. Legumes have unique vegetative and floral complexities. Our understanding of the molecular basis of flower initiation and development in legumes is limited. Here, we address this by using a computational approach to examine flowering regulatory genes in the soybean genome in comparison to the most studied model plant, Arabidopsis. For this comparison, a genome-wide analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 55 publications
10
106
0
1
Order By: Relevance
“…33,[36][37][38][39][40] These FT homologs of legumes are commonly classified into three clades, designated FTa, FTb, and FTc, according to phylogenetic analyses. Some of them have been demonstrated that they have an ability to promote flowering.…”
Section: )mentioning
confidence: 99%
“…33,[36][37][38][39][40] These FT homologs of legumes are commonly classified into three clades, designated FTa, FTb, and FTc, according to phylogenetic analyses. Some of them have been demonstrated that they have an ability to promote flowering.…”
Section: )mentioning
confidence: 99%
“…The first objective of this thesis, as described in Chapters 3-4, was achieved using bioinformatic approaches based on information available in the flowering literature of Arabidopsis and Soybean (Table 1.2), and also molecular biology techniques. The second objective of this thesis, also described in Chapters 3-4, was APETALA1 ( FLOWERING LOCUS T AT1G65480 (Kobayashi et al, 1999) Glyma16g26660 (Jung et al, 2012;Kim et al, 2012;Kong et al, 2010), Glyma16g04830…”
Section: Aim and Objectives Of Researchmentioning
confidence: 99%
“…Glyma08g47810 (Kim et al, 2012;Kong et al, 2010;Zhai et al, 2014) GIGANTEA (GI) AT1G22770 (Fowler et al, 1999) Glyma09g07240 (Jung et al, 2012) Glyma10g36600 (Kim et al, 2012;Watanabe et al, 2011) LEAFY ( Matsuzaki, H., Dong, S., Loi, H., Di, X., Liu, G., Hubbell, E., Law, J., Berntsen, T., Chadha, M., Hui, H., et al (2004). Genotyping over 100,000 SNPs on a pair of oligonucleotide arrays.…”
Section: Aim and Objectives Of Researchmentioning
confidence: 99%
See 2 more Smart Citations